SUCCESSFUL LEARNING AND ECONOMIC ASPECTS IN EDUCATIONAL PERSPECTIVE - H Hardika (Faculty of Education Universitas Negeri Malang, 2017)
Education is a process of empowerment, maturation, and the independent individuals so that they are able to manage themselves and their environment creatively and behave as a noble and elegant person. These are pursued through strategic ways, constructive efforts, and give opportunities for learners to create and construct their positive characters and their environment. Thus, the educational system can create individuals who have responsibilities to the environment. Keywords: economic value, learning, productivity